The Urgency of Gender-Based Humanistic Education in Learning - Kinana Dwinta Sukma; Cindy Oktariani; Muhammad Fadhli Perdana Lubis (Yayasan Zia Salsabila, 2023)
To help the younger generation be more agile in navigating the times, education is seen as a form of solution. Education is a forum for forming insightful people, substantially progressing society, nation and state. Therefore, education is needed that humanizes humans. Reflecting on this, humanist values show their urgency as an alternative that can solve this problem. The education provided by humanists is democratic, emancipatory, and focuses on the growth of human qualities both at the physical and psychological levels. Humanist education has the harmony that a person is able to develop as a whole, in harmony with all elements of humanity, and is able to recognize and respect the humanity of each person. This research uses a qualitative method with a descriptive-analytic approach and collects information using literature study. The research results show that humanist values are very important to internalize in order to avoid the negative impacts of unequal educational implementation, such as technocentrism and the commercialization of education. Internalization of humanist values can be realized through the use of learning methods, media and models that suit needs, as well as contextual learning content.